Impact of physical exercise participation on socioeconomic status: an empirical study using CGSS data - Zhao, Chenlei; Zhou, Junhua; Man, Mengmeng (Frontiers in Public Health, 2025)
IntroductionRecently, China’s rapid economic development and significant improvements in residents’ quality of life have led to the integration of physical exercise into the daily routines of the general public. While promoting health, this trend may have a far-reaching impact on individuals’ socioeconomic status (SES) through the accumulation of human, social, and economic capital. Can participation in physical exercise improve SES? If so, what are the mechanisms of influence? Are there differences among various groups?MethodTo address these questions, this study utilized data from the 2021 China General Social Survey to construct a regression model for investigation.ResultsThis study found that individuals with higher SES demonstrate greater awareness of and participation in physical exercise. Participation in physical exercise significantly increases the probability of individuals improving their SES, but the effect varies by gender, urban or rural residence, marital status, education level, and generation. Specifically, males, urban residents, married individuals, those with lower education levels, and older individuals benefit more. Mechanistic analysis suggests that health status and personal income are key mediators, with physical exercise enhancing SES through improved health and higher income.DiscussionThis study can help individuals understand how physical exercise can improve their SES. It serves as a reference for policymakers aiming to promote the coordinated and sustainable development of physical exercise and socioeconomics across different geographic regions and urban and rural environments, supporting individuals in their pursuit of higher SES.